2017
DOI: 10.1097/igc.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Conservative Managements in Young Women With Grade 2 or 3 Endometrial Adenocarcinoma Confined to the Endometrium

Abstract: Ovarian preservation has no impact on survival probability in patients with grade 2 or 3 endometrial cancer confined to the endometrium. On the contrary, physicians and patients should be aware of the worse prognosis associated with uterine preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Of these, 33 were excluded for various reasons, leaving 10 retrospective cohort studies to perform our meta-analysis [ 10 – 19 ]. We dropped one study because it might comprise the same study population as two other studies from the USA, although the data was extracted from a different database [ 11 , 19 , 20 ]. We chose to keep the two studies that analyzed data from the Surveillance, Epidemiology, and End Results program (SEER) rather than the one from the National Cancer Database ( NCDB ) due to their longer follow-up duration [ 11 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 33 were excluded for various reasons, leaving 10 retrospective cohort studies to perform our meta-analysis [ 10 – 19 ]. We dropped one study because it might comprise the same study population as two other studies from the USA, although the data was extracted from a different database [ 11 , 19 , 20 ]. We chose to keep the two studies that analyzed data from the Surveillance, Epidemiology, and End Results program (SEER) rather than the one from the National Cancer Database ( NCDB ) due to their longer follow-up duration [ 11 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…We dropped one study because it might comprise the same study population as two other studies from the USA, although the data was extracted from a different database [ 11 , 19 , 20 ]. We chose to keep the two studies that analyzed data from the Surveillance, Epidemiology, and End Results program (SEER) rather than the one from the National Cancer Database ( NCDB ) due to their longer follow-up duration [ 11 , 19 ]. We dropped another study from Taiwan because it contained patients over the upper age limit [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies reported the safety of fertility‐sparing management of grade 2 endometrial cancer . However, a recent large retrospective analysis reported an increased risk associated with uterine preservation in patients with grade 2 and 3 endometrial adenocarcinoma and suggested such management should be limited in time . Equivocal lesions should be examined by an experienced pathologist.…”
Section: Special Considerationsmentioning
confidence: 99%
“…In premenopausal women with low-grade early stage disease, ovarian preservation could be considered. 29,30 Vaginal cuff removal is not advised, nor is there any benefit from excising parametrial tissue in the usual case. Where obvious cervical stromal involvement is demonstrated preoperatively, a modified radical hysterectomy has been historically performed.…”
Section: Surgical Staging Procedures For Endometrial Cancermentioning
confidence: 99%
See 1 more Smart Citation